Constructing Autism: Norming Thought through Mathematics, Masculinity, Whiteness and Fascism - Cara-Julie Kather (Krisis, 2024)
This paper brings together neurodiversity studies with the notion of epistemic violence to form a theoretical framework to further understand and discuss Edith Sheffer’s findings on the construction of Autism as a diagnostic concept in Nazi Vienna: the Nazi Regime distinguished between worthy Autistic lives and unworthy Autistic lives, resulting in frameworks and stereotypes that are in place to this day. This project is of five intertwined dimensions: A) This paper uses the framework of epistemic violence to shine light on the construction of Autism as a diagnostic notion in Nazi Vienna. B) It brings together neurodiversity, epistemic violence and Sheffer’s historical study to further understand the interwovenness of different forms of violence with one another. C) It discusses stereotypes and conventional frameworks surrounding Autism with regards to the forms of gendered exclusion they entail and reinforce. D) I draw from critical studies of Western Mathematics to shine light on the interwovenness of this image of thought with masculine coded images surrounding Autism. E) Bringing these findings and movements together, I open up the question of whether there is an epistemic afterlife to fascism.